Differences in adolescent sexual risk-taking profiles and sexually transmitted infections in adulthood by justice systems involvement: a multigroup latent class analysis - Sharefa Duhaney; Gia Barboza-Salerno; Georgia Sasser (Discover Public Health)
Abstract Sexual and reproductive health is a key component of well-being, encompassing STIs, contraception access, and pregnancy. However, research on the prevalence of sexual risk-taking behaviors and sexual and reproductive health among people with a history of justice systems involvement (JSI) remains limited. This study addresses this gap by employing Multigroup Latent Class Analysis (MLCA) with data from Waves I, II, and IV of the National Longitudinal Study of Adolescent to Adult Health to examine: (1) typologies of adolescent sexual risk-taking behavior and associations with psychosocial sequelae, and (2) whether these typologies are consistent across JSI subgroups. Multinomial logistic regression assessed how sociodemographic characteristics, early childhood victimization, substance use, and depressive symptoms predicted LC membership. Four profiles emerged (N = 3,297, Mean Age: 15.5): Class 1: Multi-partner/Normative (17%), Class 2: low-risk (15.8%), Class 3: Abstinent (58.9%) and Class 4: Multi-partner/Early (8.3%). Individuals with JSI were 3.92 times more likely to be in Class 4 and 0.696 times less likely to be in Class 3 (p < 0.001). Early childhood victimization (without JSI: OR = 0.463, p < 0.001; JSI: OR = 0.224, p = 0.038) and depressive symptoms (without JSI: OR = 0.926, p < 0.001; JSI: OR = 0.560, p = 0.031) were associated with being in Class 3 across subgroups. For individuals with JSI, substance use (OR = 0.012, p < 0.001) decreased the odds of being in Class 3. Findings suggest interventions for those with JSI should address shared risk factors like early childhood victimization, and factors that uniquely predict typologies of adolescent sexual risk-taking in this population.